Spatial variations in geochemical characteristics of the modern Mackenzie Delta sedimentary system. (15th December 2015) - Vonk, Jorien E.; Giosan, Liviu; Blusztajn, Jerzy; Montlucon, Daniel; Graf Pannatier, Elisabeth; McIntyre, Cameron; Wacker, Lukas; Macdonald, Robie W.; Yunker, Mark B.; Eglinton, Timothy I.
Abstract: The Mackenzie River in Canada is by far the largest riverine source of sediment and organic carbon (OC) to the Arctic Ocean. Therefore the transport, degradation and burial of OC along the land-to-ocean continuum for this riverine system is important to study both regionally and as a dominant representative of Arctic rivers. Here, we apply sedimentological (grain size, mineral surface area), and organic and inorganic geochemical techniques (%OC, δ 13 C-OC and Δ 14 C-OC, 143 Nd/ 144 Nd, δ 2 H and δ 18 O, major and trace elements) on particulate, bank, channel and lake surface sediments from the Mackenzie Delta, as well as on surface sediments from the Mackenzie shelf in the Beaufort Sea. Our data show a hydrodynamic sorting effect resulting in the accumulation of finer-grained sediments in lake and shelf deposits. A general decrease in organic carbon (OC) to mineral surface area ratios from river-to-sea furthermore suggests a loss of mineral-bound terrestrial OC during transport through the delta and deposition on the shelf. The net isotopic value of the terrestrial OC that is lost en route, derived from relationships between δ 13 C, OC and surface area, is −28.5‰ for δ 13 C and −417‰ for Δ 14 C. We calculated that OC burial efficiencies are around 55%, which are higher (∼20%) than other large river systems such as the Amazon. Old sedimentary OC ages, up to 12 14 C-ky, suggest the delivery of both a petrogenic OC source (with an estimated contribution of 19 ± 9%) as well as a pre-aged terrestrial OC source. We calculated the 14 C-age of this pre-aged, biogenic, component to be about 6100 yrs, or −501‰, which illustrates that terrestrial OC in the watershed can reside for millennia in soils before being released into the river. Surface sediments in lakes across the delta ( n = 20) showed large variability in %OC (0.92–5.7%) and δ 13 C (−30.7‰ to −23.5‰). High-closure lakes, flooding only at exceptionally high water levels, hold high sedimentary OC contents (>2.5%) and young biogenic OC with a terrestrial or an autochthonous source whereas no-closure lakes, permanently connected to a river channel, hold sediments with pre-aged, terrestrial OC. The intermediate low-closure lakes, flooding every year during peak discharge, display the largest variability in OC content, age and source, likely reflecting variability in for example the length of river–lake connections, the distance to sediment source and the number of intermediate settling basins. Bank, channel and suspended sediment show variable 143 Nd/ 144 Nd values, yet there is a gradual but distinct spatial transition in 143 Nd/ 144 Nd (nearly three ε units; from −11.4 to −13.9) in the detrital fraction of lake surface sediments from the western to the eastern delta. This reflects the input of younger Peel River catchment material in the west and input of older geological source material in the east, and suggests that lake sediments can be used to assess variability in source watershed patterns across the delta.